(untitled) (Research, Society and Development, 2021)
The purpose of the work is to present a bibliographic review on biological activities in plants of the species Spilanthes acmella (L.). The research was carried out from September to November 2019 and consisted of a search of the SciFinder database, considering the articles published between January 1959 and August 2019 and using the keywords: Acmella oleracea, Spilanthes acmella, antioxidant, antipyretic and anti-inflammatory. Through this process resulted in 32 articles found endorsing the biological activities that are attributed to the species Spilanthes acmella (L.), such as insecticidal and anti-inflammatory activities. Many activities that are attributed to the plant Spilanthes acmella could be proven, as well as the biologically active substances and their mechanisms of action, in particular the insecticidal activity, which demonstrated great potential against several species of invertebrates.